Efektifitas Ceramah Booklet dan Buzz Group dalam Upaya Pencegahan Pneumonia pada Anak - Nababan, Sudarwati; Agushybana, Farid; Suryoputro, Antono (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: In 2016 Kopeta Health Center was ranked the 4th highest number of cough disease not pneumonia and pneumonia cases from 23 Puskesmas in Sikka District. Health education on pneumonia in this health center has often been conducted, but it seems that the results have not been effective in improving the knowledge of mothers. This is due to the fact that it is only prioritized for mothers who come as their childrenâ€™s illness and information provision has not been improving the knowledge of mothers on child pneumonia prevention. This study aims to compare the effectiveness of booklets provision and buzz group methods to increase knowledge, attitudes and practices of mothers in the prevention of pneumonia in children.Method: This study employed a quasi experimental design with non-equivalent control group. The sample of this study is the mothers who have children 0-5 years old, in Nangalimang and Kabor villages and 90 mothers were selected by using systematic random sampling technique.Â  Data was collected using face to face interview by trained enumerators guiding with close-ended questionnaire that has been validated. Data were then analyzed by Chi-Square test and Manova Post Hoc Tukey.Results: Pneumonia lectures followed by giving booklets and buzz group discussion were effective in increasing maternal knowledge and attitudes in the prevention of children pneumonia. Whereas, buzz group were more effective in improving the practice of mothers in the prevention of pneumonia than the provision of booklets. This is because the buzz method makes mothers more actively participate and creative in solving pneumonia problems by looking at other mothers' experiences. It is recommended that using buzz group lectures as an alternative method in efforts to health education for mothers, especially in the prevention of children pneumonia.Â